Influence of the combined effect of desensitizing dentifrices and universal adhesives on dentin bond strength under erosive conditions - Fabiana Tavares Lunardi PALHARI; Laís da Mata ALMEIDA; Priscila Christiane Suzy LIPORONI; Leandro Augusto HILGERT; Rayssa Ferreira ZANATTA (University of São Paulo, 2023)
Abstract Objective This study aimed to evaluate whether the use of desensitizing dentifrices containing obliterating agents can affect bond strength of eroded/abraded dentin. Methodology A total of 100 dentin samples were obtained from human molars. The teeth were cut into 3 mm-thickness discs and allocated in five groups (n=20), according to the toothpaste used: WoF - abrasion with fluoride-free toothpaste (Cocoricó); Arg - toothpaste containing arginine (Colgate Sensitive Pro-Relief); Nov - calcium sodium phosphosilicate toothpaste (Sensodyne Repair and Protect); SnF - fluoride-containing toothpaste (AmF/SnCl2/SnF2 - Elmex Erosion); and Control (no erosive/abrasive process). The erosive/abrasive cycle consisted of immersion in citric acid (1%, pH 2.6, 5 min, 4×/day) and abrasion (2×/day, 120-20 sec abrasion, 100 sec immersion) with each toothpaste. During intervals, samples were immersed in artificial saliva. This cycle was performed for five days. Two resin cylinders (2 mm in diameter) were constructed on each sample for the shear bond strength test using a universal adhesive system. The self-etch and etch-and-rinse (Scotchbond Universal) strategies were employed, each in half of the total sample (n=10). Bond strength (MPa) was measured in a shear test and failure modes were assessed with a stereomicroscope. Statistical analysis was performed using the two-way analysis of variance (ANOVA) and Tukey tests (p<0.05). Results A statistically significant difference was found between the adhesive strategies tested (p<0.001), with the self-etching form showing higher values than the etch-and-rinse. Moreover, no significant differences were observed between the tested toothpastes (p=0.750) and interactions (p=0.438). Conclusion The use of toothpaste containing obliterating agents does not affect bond strength to dentin subjected to erosive/abrasive conditions when a universal adhesive is used. However, the self-etch strategy might be preferred for eroded/abraded dentin.